2020
DOI: 10.3390/jcm9092777
|View full text |Cite
|
Sign up to set email alerts
|

Can Voice Pitch Be Preserved in Patients after Transoral Endoscopic Thyroidectomy Vestibular Approach?

Abstract: Introduction: Transoral endoscopic thyroidectomy vestibular approach (TOETVA) has become increasingly popular. Several reports have emphasized the safety and efficacy of this new approach. However, there is no report on functional voice outcomes, including voice pitch change after TOETVA. Methods: The functional voice outcomes of patients undergoing TOETVA were compared with those of patients undergoing conventional thyroidectomy. A total of 82 consecutive patients were included in the study: 44 underwent thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(42 reference statements)
0
5
0
1
Order By: Relevance
“…14,30,31 Regarding postoperative voice function, previous studies reported that the transoral vestibular approach preserved the highest frequency and pitch range better than the conventional transcervical approach. [32][33][34] The feasibility of transoral thyroidectomy using the da Vinci Si surgical system (Intuitive Surgical, Sunnyvale, CA) in humans was also reported by Kim et al 9 They utilized the three oral vestibular ports and an additional axillary port to insert the third robotic instrument. Recently, TOETVA is widely performed worldwide owing to its advantages, including short surgical time, convenience and familiarity with the surgeon's endoscopic surgery, and absence of costly robotic systems.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…14,30,31 Regarding postoperative voice function, previous studies reported that the transoral vestibular approach preserved the highest frequency and pitch range better than the conventional transcervical approach. [32][33][34] The feasibility of transoral thyroidectomy using the da Vinci Si surgical system (Intuitive Surgical, Sunnyvale, CA) in humans was also reported by Kim et al 9 They utilized the three oral vestibular ports and an additional axillary port to insert the third robotic instrument. Recently, TOETVA is widely performed worldwide owing to its advantages, including short surgical time, convenience and familiarity with the surgeon's endoscopic surgery, and absence of costly robotic systems.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, it has a midline approach that facilitates the performance of bilateral total thyroidectomy more conveniently and with complete central LN dissection, including at levels VI and VII 14,30,31 . Regarding postoperative voice function, previous studies reported that the transoral vestibular approach preserved the highest frequency and pitch range better than the conventional transcervical approach 32–34 …”
Section: Discussionmentioning
confidence: 99%
“…A total of 82 patients were included in a study published by Mi Ra Kim et al, in which 44 cases underwent TOETVA and 38 classic open methods. No significant drop in pitch was noted in TOETVA cases [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most challenging and difficult part of the surgery for an inexperienced surgeon is the dissection of the superior pole because it is poorly visible, as, during the procedure, we see the thyroid gland craniocaudal [ 37 ]. Apart from this, in our initial experience, we noticed that insertion of the first lateral port was somewhat difficult.…”
Section: Discussionmentioning
confidence: 99%
“…When TOETVA was introduced in 2016, many surgeons were concerned that injury to the external branch of the superior laryngeal nerve (EBSLN) may occur more frequently following TOETVA compared to OT because the cranio-caudal surgical view in this approach means that the sternothyroid muscle obscures visualization of the EBSLN. Recent studies have reported that using various strategies for a safe approach to the superior thyroid gland pole structures can preserve EBSLN during TOETVA [2][3][4]. However, there are still concerns that voice outcomes following TOETVA may be inferior to those of OT.…”
mentioning
confidence: 99%